The Effectiveness of Vitamin D Supplementation on Oxidative and Inflammatory Markers in Patients Suffering from End-stage Renal Disease, a Randomized Controlled Trial: Vitamin D and Oxidative and Inflammatory - Ahmed Sharif, Dana (Cellular and Molecular Biology, 2022)
Vitamin D insufficiency is common in patients suffering from end-stage renal disease (ESRD). In contrast, vitamin D supplementation could improve the status of ESRD patients (ESRDP). However, this effect’s molecular mechanism is not fully understood. Therefore, this study aimed to assess vitamin D supplementation’s impact on inflammation and oxidative signaling pathways in ESRDP. 104 ESRDP were divided into placebo (53) and vitamin D (51) groups. They were also categorized into four subgroups based on the severity of vitamin D deficiency. The dose of vitamin D3 (0.25-0.5mg/day) supplementation was determined based on plasma levels of calcium and parathyroid hormone (PTH). Vitamin D supplementation was performed for eight weeks. Serum levels of calcium, phosphorus, PTH, albumin, creatinine, ALP, and glomerular filtration along with antioxidant enzymes, malondialdehyde, and pro-inflammatory factors were measured. Moreover, the Nrf2 and NF-ĸB expression was evaluated in whole blood. According to the results, vitamin D supplementation improved the status of patients with ESRD significantly as compared with the placebo group (p<0.05). In addition, the expression of NF-ĸB and the serum levels of pro-inflammatory factors and malondialdehyde were significantly reduced. Finally, the expression of Nrf-2 and the serum of antioxidant enzymes were raised in the vitamin D group as compared with the placebo group (p<0.05). Vitamin D reduces clinical and metabolic symptoms in ESRDP by modulating gene expression (in oxidative stress and inflammation).